Rachael Ray's big orange book - Ray, Rachael; Rupp, Tina. (New York : Clarkson Potter/Publishers, 2008)
The indefatigable cooking star's ultimate labor of love, her Big Orange Book includes more than 200 all-new 30-minute recipes for the busy cook.
30-minute meals -- Entree burgers -- Vegetarian meals -- Kosher meals -- Meals for one -- A little more than 30 minues but well worth it -- From my family to yours -- Starters and snacke -- Holiday menus.
Includes index.
Keywords: Quick and easy cooking